2022
DOI: 10.1093/mnras/stac045
|View full text |Cite
|
Sign up to set email alerts
|

A full spectral-timing model to map the accretion flow in black hole binaries: the low/hard state of MAXI J1820+070

Abstract: The nature and geometry of the accretion flow in the low/hard state of black hole binaries is currently controversial. While most properties are generally explained in the truncated disc/hot inner flow model, the detection of a broad residual around the iron line argues for strong relativistic effects from an untruncated disc. Since spectral fitting alone is somewhat degenerate, we combine it with the additional information in the fast X-ray variability and perform a full spectral-timing analysis for NICER and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 88 publications
6
31
0
Order By: Relevance
“…It is worth noting that the characteristic frequency of 𝐿 4 above 90 keV is almost five times the frequency in 1-10 keV (from ∼ 2 Hz to ∼ 10 Hz). Similar results in LE band can be found in Kawamura et al (2022). They used NICER data to study the relationship between asymmetric Lorentzian function P1, P2 and energy which actually reflects the evolution of characteristic frequency with energy for 𝐿 2 , 𝐿 3 and 𝐿 4 components (P1 corresponds 𝐿 2 ; P2 corresponds 𝐿 3 and 𝐿 4 ) .…”
Section: Evolution With Spectral Hardnesssupporting
confidence: 64%
See 4 more Smart Citations
“…It is worth noting that the characteristic frequency of 𝐿 4 above 90 keV is almost five times the frequency in 1-10 keV (from ∼ 2 Hz to ∼ 10 Hz). Similar results in LE band can be found in Kawamura et al (2022). They used NICER data to study the relationship between asymmetric Lorentzian function P1, P2 and energy which actually reflects the evolution of characteristic frequency with energy for 𝐿 2 , 𝐿 3 and 𝐿 4 components (P1 corresponds 𝐿 2 ; P2 corresponds 𝐿 3 and 𝐿 4 ) .…”
Section: Evolution With Spectral Hardnesssupporting
confidence: 64%
“…As Figure 13 shows, the characteristic frequency of 𝐿 2 component shows energy-dependence: the emitting region spans from ∼ 34𝑅 𝑔 to ∼ 27𝑅 𝑔 corresponding to 1-150 keV photon energy. Like Dziełak et al (2021) and Kawamura et al (2022) indicated, with frequency-resolved spectral analysis, the 𝐿 2 component is supposed to come from variable disc emission. However, making use of the ME and HE data from Insight-HXMT, we actually detect the emission from high energy emission > 100 keV from the 𝐿 2 component which cannot be attributed to a simple standard accretion disc.…”
Section: Evolution Of the Fractional Rms And Characteristic Frequency...mentioning
confidence: 99%
See 3 more Smart Citations